Nutritional, phytochemistry, antioxidant, and antidiabetic potentials of Hippocratea velutina (Afzel.) leaves: In vitro, ex vivo and in silico studies - Adesoji Alani Olanrewaju; Akingbolabo Daniel Ogunlakin; Uchenna Obike; Gideon Ampoma Gyebi; Oluwafemi Adeleke Ojo; Omowumi Temitayo Akinola; Olayemi Elizabeth Arigbede; Abdullahi Adeyemi Adegoke; Queeneth Abiola Ogunniyi; Oluyomi Stephen Adeyemi; Mubo Adeola Sonibare (Elsevier, 2024)
Background: Hippocratea velutina is a novel folk plant that is used for lowering blood glucose and is hence a potential source of new antidiabetic medication. Therefore, this study was designed to investigate the antidiabetic and antidiabetic potential of the methanol extract of Hippocratea velutina leaves. Methods: The nutritional, elemental, and phytochemical properties of H. velutina leaves were investigated. 1,1-diphenyl-2-picrylhydrazine (DPPH) scavenging ability, Fe2+chelation and nitric oxide scavenging abilities, FeSO4-induced pancreatic injury parameters such as catalase, GSH, ENTPase, Na/K ATPase activities, α-glucosidase and α-amylase inhibitory activities were used to assess the antioxidant and antidiabetic properties of H. velutina leaf. Furthermore, HPLC-identified constituents of H. velutina leaf methanol extract were docked against human α-glucosidase (3TOP) and human α-amylase (1B2Y). Results: The results revealed that H. velutina contains protein, crude fat, flavonoids, anthraquinones, magnesium, sodium, and iron. Compared with quercetin, H. velutina significantly scavenged NO• radicals and chelated Fe2+. H. velutina exhibited a greater inhibitory effect on FeSO4-induced pancreatic injury. Furthermore, H. velutina showed a dose-dependent increase in the activity of ENTPDase and the Na/K ATPase enzyme, and it also had a significantly greater inhibitory effect on α-amylase and α-glucosidase enzymes than metformin. Computational study revealed that lutein showed the highest binding free energy to 3TOP, while apigenin offered the highest binding free energy to 1B2Y. Conclusion: Hippocratea velutina leaf possesses significant antioxidant and antidiabetic activities.